Theoretical difference between impact factor and influence factor - Pečarić, Đilda (Array, 2009)
Bibliometric constructions of "knowledge maps" and "cognitive structures of science" do not differentiate between impact and influence factors. The difference can be constructed according to different meaning and interpretation of the terms reference and citation. Reference is "acknowledgment which one author gives to another", whereas citation is "acknowledgment which one document receives from another". Development of Information Science according to period and subject area is analyzed on the corpus of citation literature retrieved from doctoral dissertations in Information Science from 1978 to 2007 at Croatian universities. The research aim is to indicate the difference between document impact factor and author's influence factor (i.e. reference ability to produce effects on actions, behavior, and opinions of authors of doctoral theses). The influence factor serves to distinguish the key role of cited authors in time and according to the duration of the influence (the average age for cited papers of dominant authors in different periods is between eight and ten years). The difference between linear and interactive communication seems vital for the interpretation of cited half-life, i.e. the attitude of one science community towards used information resources and cognitive heritage. The analyzed corpus of 22, 210 citations can be divided into three communication phases according to influence factor criteria: in the phase of dialogue and interactive communication 25% of bibliographic units are cited in the first four years ; in the second phase another 25% of units are cited from the fifth to the ninth year ; after ten years, in the dominant linear communication phase, approximately 30% of units are cited